2016
DOI: 10.1155/2016/2483041
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in LEMD3 (Man1) Associated with Osteopoikilosis and Late-Onset Generalized Morphea: A New Buschke-Ollendorf Syndrome Variant

Abstract: Introduction. Buschke-Ollendorf syndrome (BOS) is an uncommon syndrome characterized by osteopoikilosis and other bone abnormalities, accompanied by skin lesions, most frequently connective tissue nevi. BOS is caused by mutations in the LEMD3 gene, which encodes the inner nuclear membrane protein Man1. We describe a unique case of osteopoikilosis associated with late-onset localized scleroderma and familial LEMD3 mutations. Case Report. A 72-year-old woman presented with adult-onset diffuse morphea and bullous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…We further noted from previous studies that dermatofibrosis lenticularis disseminata present in the proband was the most prevalent manifestation among BOS patients. 5 The two base pair deletion c.1019_1020del, p.A340Gfs à 7 identified in our report can be presumed to be a pathogenic variant according to the American College of Medical Genetics guidelines for variant interpretation. 7 This pathogenic variant occurring downstream of the LEM domain of MAN1 protein can be predicted to result in premature truncation of the protein leading to the elimination of the C-terminal, SMAD interacting region of MAN1.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We further noted from previous studies that dermatofibrosis lenticularis disseminata present in the proband was the most prevalent manifestation among BOS patients. 5 The two base pair deletion c.1019_1020del, p.A340Gfs à 7 identified in our report can be presumed to be a pathogenic variant according to the American College of Medical Genetics guidelines for variant interpretation. 7 This pathogenic variant occurring downstream of the LEM domain of MAN1 protein can be predicted to result in premature truncation of the protein leading to the elimination of the C-terminal, SMAD interacting region of MAN1.…”
Section: Discussionmentioning
confidence: 72%
“…Pathogenic alterations in LEMD3 cause loss of the function of MAN1 protein resulting in abnormal regulation of the TGF-β/BMP signaling, thus augmenting the elastin production in the fibroblasts of the skin. [3][4][5][6] Although the proband and his father harbored the same pathogenic variant, they expressed different phenotypes suggestive of pleiotropy, a well-observed event in BOS. We further noted from previous studies that dermatofibrosis lenticularis disseminata present in the proband was the most prevalent manifestation among BOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ursächlich wird u. a. ein genetischer Defekt diskutiert [10]. Dabei wird eine Mutation im LEMD3-Gen für das gleichzeitige Auftreten der Dermatofibrosis lenticularis disseminata (Buschke-Ollendorff-Syndrom) verantwortlich gemacht [11,12]. Zuweilen tritt die Osteopoikilie gemeinsam mit der vermehrten Neigung zu Keloidbildung, der Keratoma hereditarium dissipatum palmare et ▶Abb.…”
Section: Diskussionunclassified
“…Recently, whole-genome linkage analysis of affected individuals resulted in identification of a loss-of-function mutation in gene LEMD3 at position 12q14.3. LEMD3 is believed to function in bone morphogenetic protein (BMP) signaling by interacting with the family of SMAD proteins downstream from transforming growth factor-beta (TGF-beta) to regulate bone formation (4,5). It has been reported that LEMD3 can antagonize both BMP and TGF-beta signaling in human cells (6).…”
Section: Figurementioning
confidence: 99%